(untitled) (Swiss Medical Weekly, 2011)
OBJECTIVES:The sero-prevalence of co-infection with the hepatitis B virus (HBV) and the hepatitis D virus (HDV) is well known in many European countries, starting from 6.8% in Germany to more than 27% in some Turkish areas. To gain a better description of this infection in Switzerland, and to characterise those affected, a questionnaire was sent to all Swiss gastroenterologists, hepatologists and infectologists. METHODS:A questionnaire was received by 349 physicians which asked them to report on all HBV- and HDV-infected patients seen at their units/offices. RESULTS:A total of 101 HDV-positive patients seen by 78 specialists were analysed. The physicians were in charge of 1’699 patients with chronic hepatitis B, giving a 5.9% prevalence of HDV infection in HBV-positive patients. A predominance of males (75%) from Switzerland (39%), and of African origin (21%) was recorded. Most had been contaminated by intravenous drug use (62%), followed by vertical transmission (15%), sexual contact (13%) or transfusion with blood or blood products (2%). The majority (74%) had a very low (<103 UI/ml) HBV viral load and 75% were HBeAg-negative. A total of 76% percent of those who had a liver biopsy had significant fibrosis (≥F2), and only 21% had received standard therapy (interferon or pegylated interferon-α). Overall, 10% recovered spontaneously (anti-HBs-positive). CONCLUSION:With a prevalence of 5.9% of hepatitis D in HBsAg-positive patients, Switzerland seems less affected than most other European countries, however, it is possible that this infection is under-diagnosed. Intravenous drug use was the main risk factor. Associated advanced liver disease was also very common.